2011
DOI: 10.1088/1009-0630/13/1/17
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pulsed Plasma in a Crossed Flow Dielectric Barrier Discharge Reactor for Improvement of NOxRemoval in Raw Diesel Engine Exhaust

Abstract: Improved performance of plasma in raw engine exhaust treatment is reported. A new type of reactor referred to as of cross-flow dielectric barrier discharge (DBD) was used, in which the gas flow is perpendicular to the corona electrode. In raw exhaust environment, the cross-flow (radial-flow) reactor exhibits a superior performance with regard to NOX removal when compared to that with axial flow of gas. Experiments were conducted at different flow rates ranging from 2 L/min to 25 L/min. The plasma assisted barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Therefore, plasma has not been powerful enough to make any significant variation in nitrogen oxide concentrations before this point. It was found that NO is oxidised to NO 2 due to the existence of different active oxygen species and ozone as it is reported on previous studies (Mohapatro and Rajanikanth 2011;Arai et al 2004;Fitzsimmons et al 1999). NO concentration decreased by 72 % and NO 2 concentration increased by 77 % by applying maximum voltage at 13.5 kV during the experiments.…”
Section: Effect Of Non-thermal Plasma On No X Concentrationsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, plasma has not been powerful enough to make any significant variation in nitrogen oxide concentrations before this point. It was found that NO is oxidised to NO 2 due to the existence of different active oxygen species and ozone as it is reported on previous studies (Mohapatro and Rajanikanth 2011;Arai et al 2004;Fitzsimmons et al 1999). NO concentration decreased by 72 % and NO 2 concentration increased by 77 % by applying maximum voltage at 13.5 kV during the experiments.…”
Section: Effect Of Non-thermal Plasma On No X Concentrationsupporting
confidence: 79%
“…Furthermore, emission reduction in diesel engines at low temperature is important in some special applications of diesel engines such as mining industries where exhaust cooling occurs for safety reasons. In comparison with the numerous publications on NO x treatment by plasma (Lebouvier et al 2011;Vinh et al 2012;Arai et al 2004;Jolibois et al 2012;Mohapatro and Rajanikanth 2011;Chae 2003;Yoshida et al 2009), a limited amount of research has investigated particulate matter (Ye et al 2005;Thomas et al 2000;Babaie et al 2013) and most of it has emphasised PM mass reduction only (Yao et al 2006;Fushimi et al 2008). In this paper, the effect of plasma technique on particulate matter constitutes (soot, SOF and sulphates) and NO, NO 2 and N 2 O emission concentrations have been studied.…”
Section: Introductionmentioning
confidence: 94%
“…These electrons collide with other background gas molecules, resulting in the production of more excited species and ions. However, most of them get quickly converted to radicals [18]. Possible reaction pathways responsible for NO and NO X removal can be summarized as in the following [19]:…”
Section: A Study Of No X Removal Using Axial-flow Dbd Reactormentioning
confidence: 99%
“…The preceding works on NOx−HC−PM reduction using NTP mostly investigated using simulated gas, 5,24,34−36 filtered diesel exhaust gas, 4,[7][8][9]37 or diluted diesel exhaust gas. 15,17,26,29 Few studies have investigated the simultaneous effect of HVD on both gaseous and PM emissions from raw diesel exhaust gas that contains PM and water vapor and can affect the formation of free radicals.…”
Section: ■ Introductionmentioning
confidence: 99%